2022
DOI: 10.1101/2022.03.29.486305
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Holobiont transcriptomes for the critically endangered staghorn coral (Acropora cervicornis) from two environmentally distinct sites on Turneffe Atoll, Belize

Abstract: Historically, staghorn coral (Acropora cervicornis) was a preeminent reef-builder in the Caribbean and Tropical Western Atlantic, where it constructed extensive thickets at 5-20 m depth that supported diverse ecosystems and provided coastal populations with food, storm protection, and income from tourism. In recent decades, A. cervicornis declined precipitously, up to 97% in some localities. To reverse its decline, widespread efforts are underway to characterize the phenotypic and genetic diversity of persisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Indeed, we observed that algal gene expression plasticity was particularly high for algae associated with NS-transplanted corals. These changes in C. goreaui gene expression may be driven by lower light levels on NS reefs 78 because algae associated with BR- and FR-transplanted corals, where light levels are likely higher than NS environments 33 , 99 , exhibit more similar gene expression. Additionally, these differences in expression observed in NS-transplanted C. goreaui may be associated with other environmental factors (e.g., temperature, salinity) acting on the coral holobiont that may impact the animal-algae symbiosis at the molecular level 23 , 100 .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we observed that algal gene expression plasticity was particularly high for algae associated with NS-transplanted corals. These changes in C. goreaui gene expression may be driven by lower light levels on NS reefs 78 because algae associated with BR- and FR-transplanted corals, where light levels are likely higher than NS environments 33 , 99 , exhibit more similar gene expression. Additionally, these differences in expression observed in NS-transplanted C. goreaui may be associated with other environmental factors (e.g., temperature, salinity) acting on the coral holobiont that may impact the animal-algae symbiosis at the molecular level 23 , 100 .…”
Section: Discussionmentioning
confidence: 99%